Early Antibiotic Prophylaxis Prior to Bypass Surgery Improves Tissue Penetration - Andreas, Martin; Zeitlinger, Markus; Shabanian, Shiva; Wisser, Wilfried; Thell, Rainer; Edlinger-Stanger, Maximilian; Maier-Salamon, Alexandra; Jaeger, Walter; Kocher, Alfred; Laufer, Guenther; Hiesmayr, Joerg-Michael; Hutschala, Doris (The Thoracic and Cardiovascular Surgeon, 2019)
Background We previously identified preparation of the internal mammary artery as a risk factor significantly impairing antibiotic tissue penetration into the presternal subcutaneous tissue. We, therefore, adapted our dosing schema regarding preoperative timing to overcome this risk factor.Methods Eight patients who underwent coronary artery bypass grafting with a left internal mammary artery and vein grafts were included in this clinical trial. Cefazolin (4 g) was administered twice (3 hours and 1 hour) prior to skin incision and once during skin closure (2 g). Antibiotic concentrations were measured with subcutaneous microdialysis probes on both sternal sides. Results were directly compared with the previously published patient cohort receiving the standard schema (4 g cefazolin prior to skin incision and 2 g during closure).Results All patients (7 male, 1 female, 69 ± 7 years, 26.3 ± 3.9 kg/m2) survived the perioperative period. Mean area under the curve on the right and left sternal side was 117.0 ± 92.5 μg/mL and 114.5 ± 83.2 μg/mL, respectively (p = 0.95). This was well above the previously measured mean peak tissue concentrations without early preoperative antibiotic administration on the side of mammary artery harvesting (52.4 ± 48.5 μg/mL vs. 13.1 ± 5.8 μg/mL; p = 0.039). The %fT > minimal inhibitory concentration (MIC) for Staphylococcus epidermidis and Staphylococcus aureus during the first 10 hours in presternal tissue was ≥ 70% but did not differ compared with standard schema.Conclusions Early, additional preoperative administration of cefazolin was able to significantly increase peak tissue concentrations during surgery compared with the standard protocol. No difference, however, could be achieved in the percentage of time during which the concentration exceeded the MIC.
Keywords: coronary artery bypass grafts surgery; experimental; pharmacology; sternum; wound infection